The social fabric of the networked city - Pflieger, Géraldine (EPFL Press ; Distributed by CRC Press, 2008)
Constructed around the work of Manuel Castells on the space of places, the space of flows and the networked city, nine contributors focus on the transformation of the fabric of the networked city in terms of policies and social practices.